2023
DOI: 10.1002/jbio.202300231
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning‐based pigment analysis model trained with optical approach and ground truth assistance

Geunho Jung,
Semin Kim,
Jongha Lee
et al.

Abstract: This study introduces an integrated training method combining the optical approach with ground truth for skin pigment analysis. Deep learning is increasingly applied to skin pigment analysis, primarily melanin and hemoglobin. While regression analysis is a widely used training method to predict ground truth‐like outputs, the input image resolution is restricted by computational resources. The optical approach‐based regression method can alleviate this problem, but compromises performance. We propose a strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…In this study, we utilized the revised training framework and the ResUNet++ model structure. Additionally, in our previous research, 25 we confirmed that applying ground truth for the pigments could further improve performance. However, given the considerable usability benefits of using the optical method in place of the ground truth, we chose not to use ground truth for the pigments in this study.…”
Section: Methodssupporting
confidence: 78%
“…In this study, we utilized the revised training framework and the ResUNet++ model structure. Additionally, in our previous research, 25 we confirmed that applying ground truth for the pigments could further improve performance. However, given the considerable usability benefits of using the optical method in place of the ground truth, we chose not to use ground truth for the pigments in this study.…”
Section: Methodssupporting
confidence: 78%